2016
DOI: 10.1155/2016/4928081
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Stress Resilience through Inoculation

Abstract: Stress is a generalized set of physiological and psychological responses observed when an organism is placed under challenging circumstances. The stress response allows organisms to reattain the equilibrium in face of perturbations. Unfortunately, chronic and/or traumatic exposure to stress frequently overwhelms coping ability of an individual. This is manifested as symptoms affecting emotions and cognition in stress-related mental disorders. Thus environmental interventions that promote resilience in face of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 75 publications
5
28
0
1
Order By: Relevance
“…The authors suggested that stress inoculation (i.e., resilience to stress) may be a factor. This is supported in other literature, which indicates that overcoming a number of challenging stressful events develops individuals' ability to successfully cope with subsequent stressors (Ashokan et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The authors suggested that stress inoculation (i.e., resilience to stress) may be a factor. This is supported in other literature, which indicates that overcoming a number of challenging stressful events develops individuals' ability to successfully cope with subsequent stressors (Ashokan et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Researchers have also suggested that individual factors, such as personality and social variables, influence the development of resilience to stress (Ashokan et al, 2016;Joseph & Linley, 2006). Thus, it is possible that, due to the stressful nature of police work in addition to the stressors present in the aftermath of Hurricane Katrina, the officers in the current study may have habituated to stressful events over time.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Prior research indicates inoculation is impacted by several factors including timing and severity of initial PTEs and individual differences in coping (Agaibi and Wilson 2005;Ashokan et al 2016;Fossion et al 2014;Seery 2011). Though most research on stress-inoculation focuses on adverse childhood events, exposure to moderately severe PTEs in adulthood may also foster subsequent psychological Btoughness^ (Seery 2011).…”
Section: Stress-inoculation Theorymentioning
confidence: 99%
“…In addition, the neurobiological mechanisms that underlie resilient functioning may depend on the severity of CM exposure. Specifically, milder and more manageable levels of stress might have a 'steeling' effect on the individual, thus promoting resilient outcomes to future stress, a phenomenon described as stress inoculation (Ashokan, Sivasubramanian, & Mitra, 2016;Banihashemi et al, 2015;Catalani et al, 2011;Elder GH Jr, Liker JK, 1984;Khoshaba & Maddi, 1999;Macrì, Zoratto, & Laviola, 2011;Oldehinkel, Ormel, Verhulst, & Nederhof, 2014;Parker, Buckmaster, Justus, Schatzberg, & Lyons, 2005;Parker, Buckmaster, Schatzberg, & Lyons, 2004;M Rutter, 1993). In contrast, high levels of stress have been associated with stress amplification/sensitisation or calibration effects (Catalani et al, 2011;Macrì et al, 2011;Oldehinkel et al, 2014;Seery, 2011), see for extensive overviews (Del Giudice, Ellis, & Shirtcliff, 2011;Sih, 2011).…”
Section: Discussionmentioning
confidence: 99%